Correction to: Safeguarding and using global banana diversity: a holistic approach - Ines Van den Houwe; Rachel Chase; Julie Sardos; Max Ruas; Els Kempenaers; Valentin Guignon; Sebastien Massart; Sebastien Carpentier; Bart Panis; Mathieu Rouard; Nicolas Roux (CABI Agriculture and Bioscience)
An amendment to this paper has been published and can be accessed via the original article.